Nuove scoperte de'Russi al nord del Mare del Sud sí nell' Asia, che nell' America. - Zatta, Antonio, active 1757-1797 (Zatta, Antonio, active 1757-1797, 1776)
18th century Copper engraving handcolored with watercolor. The paper contains a watermark. Outline color. Relief shown by hachures. Printed in lower left corner: "Nuove scoperte de'Russi al nord del Mare del Sud sí nell' Asia, che nell' America. Venezia 1776. Presso Antonio Zatta. Con Privilegio dell' Eccmo Senato." Printed above top border in center: "Le Parti del Nord-est dell' Asia, e del Nord-ouest dell' America, non erano conosciute, senon per via di mere conghietture; ma dacché coll' andare dé' tempi se ne fecero rilevanti scoperte, si giunse a formare il presente nuovo sistema geografico delle Partí stesse, ch' a' 31. d.' Agosto 1774 su approvato dalla Reale Accademia delle Scienze di Parigi, sperando si, che con le recenti spedizioni fatte dagli Spagnoli al Nord della California, e dall' altre degl' Inglesi dalla Baja d'Hudson per entrare nel Mare del Sud per il Nord dell' America, si metteranno i Geografi in istato di dare delle nuove produzioni." Printed in lower right is an explanation of coordinates for a Northwest Passage: "*Luogo, in cui dagl' Inglesi fú osservato il passaggio di Venere nel 1769. a gradi 283. 27'.di Longitudine, e 58. 47'.3''2di Latitudine. Vedi Fe. Del Principe di Galles. **In questo luogo fú osservato il passaggio di Venere nel 1769 dal fú Ab. Chappe a gradi 267.59'.30".di Longitudine, e 23.36'. di Latitudine. Vedi. S. Giuseppe." Depicts northwest North America and northeast Asia including the North Pacific Ocean, the Kamchatka Peninsula, the Aleutian Islands, California and Canada. Of note, the map shows an inaccurate depiction of northwest North America, displaying the fabled Northwest Passage. Depicts Alaska as unnamed, although it is labeled "Costa scoperta da Beering Tchirikow nel 1741." Also shows the Strait of Anian, the mythical land of Quivira, and Nuova Albione in northern California. Shows the "Bella Riviera" flowing from the interior of North America to the northwest coast. Also shows the "Fiume de lost Estrechos o Grande F. che scorre all' Ouest" flowing from the "L. Salso" or Salt Lake into the Pacific Ocean. Includes notes on exploration by Abbe (?) Chappe d'Auteroche, Bering, Tchirikov, and Cluny. The illustration in the lower left corner shows a sailing ship just off of an island inhabited by a crocodile, an elephant, and a large bird possibly an ostrich. br> Scale: c.a. 1: 25,000,000. Antonio Zatta (fl. 1757-1797) was an Italian publisher who lived in Venice. His major works include 4 volumes of "Atlante Novissimo" (1775-85), "Europe" (1777) and "Nuovo Atlante" (1799) (Tooley, 681-2). This particular map was published in "Atlante Novissimo," vol. 4, no. 50 (Lowery, 381, WL 581; Wheat, 225, entry 167). For the most part, Zatta follows the work of Robert de Vaugondy with the exception of including new names in the south (Wagner, entry 654, 344). The map shows a number of strange place names and apocryphal accounts from Baron Louis Armand de Lom d'Arce de Lahontan and Admiral Bartolomé de Fonte. Such information is seen in the inclusion of the "Mozemleks" and the "Gnacsitares." Portinaro and Knirsch note that the map provides an "eerily distorted…map … that purports to show the latest information gathered by the Russians and Bering about the Alaska area but it is difficult to make out what is being represented" (Portinaro and Knirsch, 250). Source(s): Henry E. Huntington Library. Catalog Record. Accessed 9 Feb 2009. Lowery, Woodbury. "The Lowery Collection: A Descriptive List of Maps of the Spanish Possessions within the Present Limits of the United States, 1502-1820." Washington, D.C.: Government Printing Office, 1912. Portinaro, Pierluigi and Franco Knirsch. "The Cartography of North America 1500-1800." New York: Facts on File, Inc., 1987. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979. University of California Libraries. Catalog Record. Accessed 10 Feb 2009. Wagner, Henry R. "The Cartography of the Northwest Coast of America to the year 1800 Volume 2." Berkeley: University of California Press, 1937. Wheat, Carl I. "Mapping the Transmississippi West." Volume 1. San Francisco: Institute of Historical Cartography, 1957.